Teachers’ Attitudes toward Integrating Children with Physical Disabilities in Public Schools in Northern Saudi Arabia - Bataineh, Osama; Rwaili, Mad allah (Jordan Journal of Educational Sciences, 2015)
The objective of this study was to identify teachers’ attitudes in northern Saudi Arabia toward integrating children with physical disabilities in the public school sector in addition to measuring these attitudes with respect to the following variables: gender, degree credentials and years of work experience. The elementary public sector consists of 14,531 elementary school teachers in the following towns: Al Qarrayat, Tabouk and Aaraar of northern Saudi Arabia; 7721 are males and 6810 are females as per the statistical records of the Ministry of Education in Saudi Arabia. The sample for this study consists of 768 female and male teachers which corresponds to 5.3% of the total number of teachers in the elementary public school sector of northern Saudi Arabia. The participants in this study were randomly chosen. The researchers designed a questionnaire to measure teacher’s attitudes toward integrating children with physical disabilities in the public schooling sector of northern Saudi Arabia. The reliability and validity of the instrument used were satisfied using proper statistical procedures. The results revealed positive attitudes toward integrating children with physical disabilities in the public school sector with significant differences with respect to two variables in this study: gender and years of experience; the difference was measured in terms of (coefficient α = 0.05) in favor of male teachers and 1-5 years of work experience over the other categories. There were no significant differences with respect to degree qualification